BUILDING COOPERATION AND BRANDING IMAGE OF EDUCATIONAL INSTITUTIONS: MEMBANGUN KERJASAMA DAN BRANDING IMAGE LEMBAGA PENDIDIKAN - EL WAHYU, MUHAMMAD; Fauzi, Syahrul (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2025)
This research study is motivated by the importance of building collaboration both internally and externally to be able to develop every educational institution and achieve the planned goals. This study aims to analyze the relationship between educational institution cooperation and the branding image approach in educational institutions. This study uses a qualitative-descriptive method with the type of library research, the references used are books and relevant articles. The results of the study reveal that collaboration and branding image are two things that cannot be separated from one another because they both have the goal of developing and advancing a particular educational institution.